2020
DOI: 10.21203/rs.3.rs-18096/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and CT imaging characteristics of COVID-19 cases in Wenzhou city: A retrospective analysis

Abstract: Background: In December 2019, Wuhan witnessed the outbreak of an “unexplained pneumonia” caused by a novel coronavirus strain infection and was dubbed the COVID-19 by the WHO. The disease quickly spread to China. This study aimed to investigate the disease’s evolving epidemiological history, as well as analyze the clinical and CT imaging characteristics, treatment regimens, and patients’ prognosis.Methods: This was a retrospective study whose cases were 64 patients with a confirmed diagnosis of COVID-19. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…The retrospective studies examined demonstrated a high sensitivity rate for CT chest compared with RT‐PCR in symptomatic COVID‐19 patients [15–17,21–32]. The largest study to date, by Ai et al ., is a retrospective analysis which included 1014 patients who were being tested for COVID‐19 in Wuhan, China [26].…”
Section: Resultsmentioning
confidence: 99%
“…The retrospective studies examined demonstrated a high sensitivity rate for CT chest compared with RT‐PCR in symptomatic COVID‐19 patients [15–17,21–32]. The largest study to date, by Ai et al ., is a retrospective analysis which included 1014 patients who were being tested for COVID‐19 in Wuhan, China [26].…”
Section: Resultsmentioning
confidence: 99%
“…Hasil penelitian dari literatur ke-8 oleh Fu et al, 2020 14 di China mendapatkan hasil dari 64 pasien, 58 diantaranya memiliki temuan abnormal pada pemeriksaan CT scan toraks. CT scan pertama (dalam 2 hari) memiliki sensitivitas yang lebih tinggi dari RT-PCR dalam mendeteksi COVID-19 yaitu sekitar 85,9% untuk CT scan toraks dan 56,3% untuk RT-PCR.…”
Section: Hasil Penelitianunclassified